2011
DOI: 10.3892/etm.2011.202
|View full text |Cite
|
Sign up to set email alerts
|

Valproate inhibits colon cancer growth through cell cycle modification in vivo and in vitro

Abstract: Abstract. Valproate (Vpa) is a well-characterized histone deacetylase inhibitor with anti-neoplastic properties. We analyzed the growth blocking effects and the molecular mode of action of this compound in colorectal cancer cells in vitro and in vivo. caco-2, SW-480, cx-1 or Widr cell lines were exposed to Vpa (0.25-2 mm) for various time periods. cell growth, cell cycle progression and apoptosis were analyzed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide dye reduction assay and flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Cell-cycle progression is regulated by a series of checkpoint proteins. Elevated expressions of cyclin D1, cyclin E, and c-Myc have been reported in colon cancer [20]. Modification of the cell cycle has been considered as an important therapeutic strategy for colon cancer treatment [20].…”
Section: Discussionmentioning
confidence: 99%
“…Cell-cycle progression is regulated by a series of checkpoint proteins. Elevated expressions of cyclin D1, cyclin E, and c-Myc have been reported in colon cancer [20]. Modification of the cell cycle has been considered as an important therapeutic strategy for colon cancer treatment [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated GSK3 as a potential therapeutic target for cancer treatment, such as in prostate cancer (43), melanoma (30), glioblastoma (44), pancreatic cancer (45), and colorectal cancer (46). Some studies have also evaluated the therapeutic effect of VPA on colorectal cancer (47,48) through inhibiting the enhanced histone deacetylase activity; however, such studies did not refer to its effect as a GSK3 inhibitor. None of these previous reports suggested the potential of GSK3 inhibition as a CSC-targeting therapy.…”
Section: Discussionmentioning
confidence: 99%
“…valproic acid, estradiol, and gefitinib) by querying CMap to restore the normal expression of five targets. Notably, the valproic acid not only inhibits CRC cells growth through cell cycle modification but also has the ability to reverse aberrant DNA methylation partially (Strey et al, 2011;Brodie and Brandes, 2014;Bressy et al, 2017). Moreover, estradiol has been found that it reduced proliferation and apoptosis in CRC (Sasso et al, 2019).…”
Section: Design Of Multiple-molecule Drugs For Preventing the Progresmentioning
confidence: 99%